1997
DOI: 10.1093/rheumatology/36.6.643
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of serum matrix metalloproteinase 1 and matrix metalloproteinase 3 in rheumatoid arthritis patients following anti- tumour necrosis factor-alpha (cA2) therapy

Abstract: Matrix metalloproteinase (MMP)-1 and MMP-3 levels were measured in serum samples from rheumatoid arthritis (RA) patients undergoing a double-blinded placebo-controlled trial with the chimaeric anti-tumour necrosis factor (TNF)-alpha antibody cA2. Both MMP-1 (P < 0.015), but to a larger extent MMP-3 (P < 0.001) levels were elevated in all RA patients prior to the commencement of the trial compared with normal control sera. Following cA2 therapy, MMP-1 and MMP-3 levels were assessed in the placebo, and 1 and 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(77 citation statements)
references
References 0 publications
5
71
0
1
Order By: Relevance
“…In the present study, this was observed with levels of serum MMP-3, and although it is disappointing that we did not demonstrate changes in levels of other biochemical markers with MTX therapy, the study was not designed to address this question and the number of patients receiving MTX was limited. Our findings regarding serum MMP-3 levels in patients treated with MTX are consistent with the results of other studies that have shown a decrease in circulating MMP-3 levels with conventional DMARD therapy (43,44) or biologic therapy (45)(46)(47).…”
Section: Young-min Et Alsupporting
confidence: 92%
“…In the present study, this was observed with levels of serum MMP-3, and although it is disappointing that we did not demonstrate changes in levels of other biochemical markers with MTX therapy, the study was not designed to address this question and the number of patients receiving MTX was limited. Our findings regarding serum MMP-3 levels in patients treated with MTX are consistent with the results of other studies that have shown a decrease in circulating MMP-3 levels with conventional DMARD therapy (43,44) or biologic therapy (45)(46)(47).…”
Section: Young-min Et Alsupporting
confidence: 92%
“…It has also been reported that serum MMP-1 and MMP-3 were reduced in RA patients following anti-TNF therapy (43). Based on the present results, it should be kept in mind that these patients may be at risk for the side effect of scleroderma-like symptoms.…”
Section: Tnfrp55-mediated Signaling In Pathogenesis Of Sclerodermasupporting
confidence: 72%
“…Synovial synthesis of TNFα, IL-1α and IL-1β were also reduced in RA patients following a single infusion of INF [29]. Reduced IL-1 levels result in reduced synthesis of MMP and other degradative enzymes, such as proMMP-1 and proMMP-3 [28,30,31].…”
Section: Effect On Cytokine Productionmentioning
confidence: 99%